The goodbye coast : a Philip Marlowe novel - Ide, Joe (Mulholland Books, Little, Brown and Company, 2022)
"Marlowe, against his better judgement, accepts two missing person cases, the first a daughter of a faded, tyrannical Hollywood starlet, and the second, a British child stolen from his mother by his father. At the center of The Goodbye Coast is Marlowe's troubled and confounding relationship with his father, a son who despises yet respects his dad, and a dad who's unable to hide his bitter disappointment with his grown boy"--